Analysis of the correlation between thyroid hormones and thyroid volume by gender: A volumetric computed tomography study - Serkan Oner; Yusuf Secgin; Zulal Oner; Seyma Toy (Medicine Science, 2022)
The aim of this study was to evaluate the correlation between triiodothyronine (T3), thyroxine (T4), and thyroid-stimulating hormone (TSH) hormones and thyroid gland volume with volumetric analysis performed by using computed tomography (CT) images. In this retrospective study, IV contrasted thoracic CT images taken for different indications between 2019 January and 2020 January were scanned from the archive system of the hospital. 67 (31F, 36M) individuals chosen randomly among patients whose CT results were reported as normal and who had taken thyroid hormone tests within the past week were included in the study. Images in Digital Imaging and Communications in Medicine format were transferred to the personal work station program (Horos Medical Image Viewer). By using the Region of Interest (ROI) console in the current program, a three dimensional model was obtained by drawing the border of the thyroid gland in sections varying between 15 and 25. Volume values of this three-dimensional model and TSH, T3, T4 values of the individuals were compared. While no correlation was found between thyroid gland volume and T3 and T4 hormones, a negative significant correlation was found with TSH. In terms of gender, thyroid gland volume, T3, T4 values were found to be statistically significantly higher in women when compared with men (p≤0.05). TSH value was found to be higher in women when compared with men (p=0.005). No statistically significant difference was found in T4 value (p=0.057). Radio-anatomical volumetric data of the thyroid gland presented in this study and its correlation with thyroid functions will be beneficial to clinicians working in the field in both internal and surgical medicine branches and will also guide future studies. [Med-Science 2022; 11(2.000): 810-3]